Zwierzyniec - nieznany kompleks leśny w sąsiedztwie zabytkowego parku pałacowego w Zatoniu = The Animal Park - an unknown forest area in the vicinity of the historic palace park in Zatonie - Eckert, Wojciech (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper briefly presents the history of the palace-park complex in Zatonie, which is included in the list of the monuments of the Lubusz Voivodship. The palace is in ruins, the park is devastated and neglected. However, in the close vicinity of this complex there is a very interesting forest area called the Animal Park. That area, covered with ancient forest, needs detailed examination, stock-taking and protection.
Keywords: pałac w Zatoniu; kompleks leśny; park; dobro kultury; Zwierzyniec; palace in Zatonie; forest area; heritage; Animal Park